Body Mass Index and Semen Quality in Partners of Infertile Couples - Chowdhury, Tanzeem Sabina; Chowdhury, TA (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Background: Obesity has almost doubled worldwide in the last 50 years and a great portion of these obese population are young adults. It has been proved that increased body weight has a negative correlation with female fertility. Recent studies show there has been decreasing semen quality with concurrent increase in BMI of the male partner. The aim of this study was to investigate the effect of obesity on sperm parameters among the male partners of the infertile couples from an infertility management center in Dhaka, Bangladesh. Methods: A cross sectional study was carried out in Infertility Management Center, a tertiary center for infertility management and IVF in Dhaka, Bangladesh from August to October 2016. A total of 225 men presented for infertility evaluation during this period underwent BMI calculation and semen analysis. Result: Out of 225 male partners, about two third (65.8%) belonged to age 31 to 40 years.Majority (44.4%) of the patients were overweight (25-29.9 kg/m2). The mean total sperm count was found to be 54.4+53.2 million/mL with a range from 0 to 280 million/m. The mean total motility of sperms was found to be 36.8+23.4 percent with a range from 0 to 80 percent. The mean normal morphology was found to be 42.0+22.1 % with a range of 0 to 80 percent. Regression analysis showed no correlation (r=0.003; p=0.966) between BMI and total sperm concentration but showed negative correlation with total motility (r=0.073;p=0.0277) and morphology of sperm (r=0.088; p=0.186). Conclusion: There was a negative correlation between sperm motility and morphology with higher BMI among male partners of couples seeking fertility treatment. So, male partners along with their female counterparts should be counseled about the importance of maintaining an ideal BMI for better fertility outcome. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 14-19